EFICIENCY ANALYSIS OF DRIED SHRIMP (EBI) MARKETING CHANNELS AT BAGANSIAPIAPI FISHING PORT, RIAU - Aulia Azka; Shiffa Febyarandika Shalichaty; Erlina Erlina (Berkala Perikanan Terubuk, 2021)
Shrimp has a high nutritional content and is much favored by the community. Shrimp processing in Bagansiapiapi is mostly used as dried shirmp (ebi). Ebi from Bagansiapi is not only marketed in the local market but is also marketed outside the region. Information related to marketing channels, marketing margins, marketing efficiency of dried shrimp (ebi) at the Fishing Port, Bagansiapiapi has not been widely carried out, even though this information is very necessary to see the impact of marketing on the selling price of ebi. The purpose of this study was to determine the marketing margin, share farmers, and marketing efficiency of dried shrimp (ebi) in each marketing channel. Analysis of the data used is marketing margin, farmer share, marketing efficiency. The results showed that the marketing channel of dried shrimp (ebi) at the Fisherman's Port, Bagansiapiapi, Riau Province has four marketing channels. Marketing channels I, II, III, IV have a marketing margin value of Rp.47,800, respectively; Rp. 52,800; Rp 62,800; and Rp. 52,800. The value of the farmer's share in the four marketing channels is 50% in a row; 46.15%; 40%; 461.5%. Of the four marketing channel patterns, the most efficient is the marketing channel pattern I with an efficiency level of 7.5%.